Manipulation of female stereotypes in Chinese translations of fragrance product descriptions - Zhu, Li; Ang, Lay Hoon; Mansor, Nor Shahila (Academy Publication, 2023)
Although most research examines female stereotypes in advertising, few studies focus on translating female stereotypes in advertising texts from English into Chinese. This study explores how female stereotypes are recognized in fragrance product descriptions and how they are manipulated in Chinese translations. Twelve fragrance brands with 136 product descriptions were selected, and the qualitative analysis software ATLAS.ti was used for data analysis. This research recognized female stereotypes by examining communal and agentic traits. Results indicate that the female portrayals in the source and target texts present a positive trend but are stereotypical in different aspects. Female stereotypes in the Chinese translations are overwhelmingly indicated by communal traits but surprisingly by fewer sex-related traits. Manipulative strategies account for 70% of the strategy used to render female stereotypes. These manipulative strategies include gender omission, gender addition, gender reversal, gender permutation, and gender explicitation. Cross-cultural differences could partly explain the choice of manipulative strategies. The findings ascertain translation as manipulation in rendering female stereotypes in fragrance descriptions. It may provide references for translation practitioners in their future translation practice.